Intelligent decision support system for degree selection using AHP technique - Jamil, Rokiah; Jarot, Sigit Puspito Wigati (2012)
The application process for entry into public universities in Malaysia, handled entirely by the University Centre Unit (UPU), has a major drawback as often the degree programme offered to students does not match their field of interest. The Degree Selection System (DSS) used for this study is designed to assist students to select the most appropriate degree programmes that match their field of study. The methodology used in this study is the Analytical Hierarchy Process (AHP) while Holland's Six Personality Types is used to identify the student's field of interest. The expected finding will display a list of programmes that matches the students' field of interest and they will have the freedom to choose eight of them.